Frailty and the Risk of Polypharmacy in the Older Person: Enabling and Preventative Approaches - Martin C. Nwadiugwu (Journal of Aging Research)
Frail older people have an inherent risk of polypharmacy due to the need to treat multiple comorbidities, thus leading to various negative effects on their health due to the adverse actions from the drugs. This issue was discussed from a person-centered perspective, highlighting the category of frail older adults who are at a higher risk. Appropriate medication reconciliation in this population with useful prescribing tools (Beers and START/STOPP criteria) to minimize polypharmacy and to provide alternative prescriptive intervention could go alongside primary care to reduce the extent of frailty and polypharmacy. Reducing delayed referrals and extended hospitalization with electronic health record systems and using the signs of frailty from the Electronic Frailty Index (EFI) to predict polypharmacy for frail older persons are preventative approaches that proactively respond to frailty associated with the risk of polypharmacy.